Agriculture, WASH, and safety nets: Ethiopia’s multisector story - Warren, Andrea (International Food Policy Research Institute, 2016)
OVER THE PAST 25 years, Ethiopia has made remarkable headway in addressing the country’s nutrition situation. Despite ongoing challenges, significant progress has been made toward meeting the United Nations Millennium Development Goals, including halving child mortality, doubling the number of people with access to clean water, and quadrupling primary school enrollment. Ethiopia is also on track to eradicate extreme hunger and poverty. The country was one of the top five performing countries in the 2000s in terms of reducing stunting by reducing its prevalence from 57.4 percent in 2000 to 44.2 percent in 2011, although levels remained high at 40.0 percent in 2014.2 The same 2014 Demographic and Health Survey found that a further 9 percent of children younger than 5 years old experience wasting, and only 4 percent of children meet the standards for a minimal acceptable diet (a World Health Organization [WHO]/UNICEF indicator for complementary feeding).3 Significant regional differences persist, with the highest rates of stunting (52 percent) found in Amhara and the lowest found in Gambela (27 percent) and Addis Ababa (22 percent). Overall, stunting is more prevalent in rural (46 percent) than in urban areas (36 percent).